CHALLENGES IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Munavvar Umarova; Jalolova Muqaddas (TADQIQOTLAR, 2025)
Learning English as a foreign language has become an essential skill in today’s globalized world. Many learners face various difficulties while acquiring the language, including  linguistic,  psychological,  and  environmental  challenges.  This  paper discusses  the  most  common  challenges  students  encounter  and  suggests  possible solutions to improve English language learning.